Mental toughness nelayan: analisis fenomenologis kekuatan nelayan dalam menghadapi tantangan hidup - Putra, Novan Dwi Purnama; Dewi, Kartika Sari; Sulistiani, Wiwik; Mahastuti, Dewi (Fakultas Psikologi Universitas Hang Tuah, 2026)
The issue of mental toughness among fishermen remains under-recognized by the public. Income instability due to the lean season, extreme weather, and price fluctuations puts fishermen under significant economic pressure. This study aims to understand the dynamics of fishermen's mental toughness in dealing with income instability. The study employed a qualitative phenomenological approach with Interpretative Phenomenological Analysis (IPA). Participants were three active fishermen with at least five years of fishing experience. Data were collected through in-depth interviews and observations, and their validity was tested using technical triangulation, member checking, peer debriefing, and audit trails. The results showed that fishermen's mental toughness is formed through four main dimensions (control, challenge, commitment, and confidence) with different dynamics for each participant. Fishermen with longer experience demonstrated resilience based on stability and economic planning, while fishermen with shorter experience demonstrated resilience based on adaptation and innovation, particularly in the utilization of marketing technology. These findings confirm that fishermen's mental toughness is influenced by work experience, economic adaptation strategies, and the social context of the coastal environment. This research contributes to the development of mental toughness studies in the fishing profession and becomes the basis for formulating empowerment programs and psychosocial assistance for coastal communities.